1997
DOI: 10.1021/la970196p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rotation of a Camphor Scraping on Water:  New Insight into the Old Problem

Abstract: The translational and rotational motion of a camphor scraping at an air/water interface was investigated. The characteristics of the rotation depended on the temperature, surface tension, and the chemical structure of the camphor derivative. The direction of rotation, either clockwise or counterclockwise, is determined by asymmetry in the shape of the solid camphor scraping. The essential features of the motion of a camphor scraping were reproduced by a computer simulation. The driving force on this motion is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
275
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(279 citation statements)
references
References 15 publications
4
275
0
Order By: Relevance
“…We also include a dissipation term in Eq. (8). This term, written as αu t , is given to stabilize the oscillatory motions.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We also include a dissipation term in Eq. (8). This term, written as αu t , is given to stabilize the oscillatory motions.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Spontaneous motion driven by inhomogeneity in interfacial tension is an area of study relating to active matter. [5][6][7][8][9][10][11][12][13][14][15][16] For example, alcohol droplets placed on water move spontaneously while exhibiting deformations to their shape. 17,18 Since such systems are relatively simple, it is possible to perform experiments under a broad parameter space; therefore, such a setting provides a preferable experimental framework for investigations of general aspects.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recently, we reported that the nature of the self-motion of a camphor scraping changes depending on both the internal conditions (e.g., scraping morphology and chemical structure of the camphor derivative) [21][22][23][24] and external conditions (e.g., temperature, surface tension, and the shape of the cell), [24][25][26][27][28] and the essential features of self-motion could be reproduced by a computer simulation. [21][22][23][24][25][26][27][28] In one of these studies, we reported that the mode of self-motion of a camphoric acid boat characteristically changes depending on the concentration of phosphate ion or pH in the aqueous phase, and that the characteristic mode-change between uniform, oscillatory, and no motion is coupled with the acid -base reaction. 22 In this study, we investigated the nature of self-motion depending on the reaction order of the acid-base reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As a camphor particle is placed on pure water, it exhibits spontaneous motion. The mechanism of the motion is briefly described as follows [12,13]: Camphor molecules escape from the camphor particle to the water surface. Since camphor has a surface activity, the camphor molecules at the water surface reduce the surface tension.…”
mentioning
confidence: 99%